Beginner's guide to life drawing - Armer, Eddie (Search Press Limited, 2019)
Improve your drawing skills and learn how to observe the human form with this simple practical course. By applying a few basic rules, the shape of a body can be both accurately and artistically captured in as little as two minutes, using only a small selection of artist's materials. Begin with learning to draw a simple pose, then discover a variety of sketching techniques using different media. Learn how to use line and tone, make scribble drawings, use charcoal, and tackle a range of poses and features.